Haemodynamic consequences following closure of an Abernethy malformation in a patient following a total cavopulmonary shunt. (21st February 2018) - Sasikumar, Deepa; Sasidharan, Bijulal; Ayyappan, Anoop
Abstract: A 17-year-old girl with situs ambiguous, hypoplastic right ventricle with a large ventricular septal defect, and severe pulmonary stenosis had undergone Kawashima operation 10 years back. She had significant desaturation because of a large Abernethy malformation, with reverse shunting from the inferior caval vein to the portal vein. It was closed with a vascular plug, with improvement in oxygen saturation. She developed extensive inferior caval vein thrombus following the procedure, which was managed conservatively by anti-coagulation.